Factors affecting ASEAN teacher competencies : study on pre-service teachers in Rajabhat University in Thailand - Chayapol THONGPHUKDEE; Thanin RATANA-O-LARN (My University, 2021)
This paper is reported the synthetized researches of the factors affecting ASEAN teacher competencies for Pre-Service Teachers in Rajabhat University. Content analysis was used for synthesizing 12 researches. It was found that 5 factors affecting ASEAN teacher competencies for Pre-Service Teachers in Rajabhat University. Policy Management, Curriculum Management, Self-Efficacy, Achievement Motivation, and Attitude Formation are included. The multi – level factors model was convinced into 2 levels; 1) University Level 2) Student Level. Policy Management, Curriculum Management are realized in University level. Whereas Self-Efficacy, Achievement Motivation, and Attitude Formation are apprehended in student level. The correlation of factors affecting ASEAN teacher competencies for school interns in Rajabhat University are found that Policy Management affected directly and indirectly ASEAN teacher competencies through Curriculum Management. Self-Efficacy and Achievement Motivation affected directly and indirectly ASEAN teacher competencies through Attitude Formation.
Keywords: Global Education and Multiculturalism